2015
DOI: 10.1186/s13068-015-0275-2
|View full text |Cite
|
Sign up to set email alerts
|

Restricting lignin and enhancing sugar deposition in secondary cell walls enhances monomeric sugar release after low temperature ionic liquid pretreatment

Abstract: BackgroundLignocellulosic biomass has the potential to be a major source of renewable sugar for biofuel production. Before enzymatic hydrolysis, biomass must first undergo a pretreatment step in order to be more susceptible to saccharification and generate high yields of fermentable sugars. Lignin, a complex, interlinked, phenolic polymer, associates with secondary cell wall polysaccharides, rendering them less accessible to enzymatic hydrolysis. Herein, we describe the analysis of engineered Arabidopsis lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Lignification and cross-linkage of lignin with other cell wall components form a natural barrier against the penetration of disparaging enzymes through the cell wall [42]. This barrier negatively impacts sugar release from cellulose and hemicellulose [43]. We found that a 1 % (Fig.…”
Section: Impact Of Lignin Content On Sugar Releasementioning
confidence: 76%
“…Lignification and cross-linkage of lignin with other cell wall components form a natural barrier against the penetration of disparaging enzymes through the cell wall [42]. This barrier negatively impacts sugar release from cellulose and hemicellulose [43]. We found that a 1 % (Fig.…”
Section: Impact Of Lignin Content On Sugar Releasementioning
confidence: 76%
“…Similarly, poplars downregulated in cinnamoyl - CoA reductase ( CCR ) had more facile saccharification but at a biomass yield penalty [ 8 ]. A selective reduction in lignin and increase in cellulose accumulation was shown to impact the secondary cell wall structure in Arabidopsis [ 9 ]. Recently, with the basic idea of introducing readily cleavable bonds into the lignin backbone to lower the energy requirement for biomass processing, poplar was engineered to produce monolignol ferulate conjugates to augment the monomer pool by introducing an exotic feruloyl - CoA monolignol transferase ( FMT ) genes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 ). Both R110-1.0 and R120-0.5 samples have significantly increased total sugars recovery (29.5 and 30.9 g total sugar per 100 g starting biomass) in the enzymatic hydrolysates as compared to the 8.3 and 8.4 g total sugars per 100 g starting biomass from the corresponding water pretreated samples (Table 3 , Additional file 1 ), which was higher than those of Arabidopsis pretreated with [C 2 mim][OAc] at 140 °C for 3 h [ 37 ].…”
Section: Resultsmentioning
confidence: 99%